2015
DOI: 10.1007/s10452-015-9502-y
|View full text |Cite
|
Sign up to set email alerts
|

Divergent growth patterns between juveniles of two sympatric Arctic charr morphs with contrasting depth gradient niche preferences

Abstract: Seasonal growth patterns have been investigated in juveniles of two reproductively isolated Arctic charr [Salvelinus alpinus (L.)] morphs, which coexist in distinct ecological niches (upper-water and deep-water environments) in a subarctic lake. Offspring (F1-generation) of each of the littoral spawning charr (LO) and the profundal spawning charr (PB) were reared individually over a period of 12 months under simulated natural photoperiod (at 69°N) and two different temperature regimes to mimic the profundal zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Based on recent ecological and genetic studies, deep-water morphs of Arctic charr and whitefish are replicated in several locations and appear to originate locally (Østbye et al, 2006;Knudsen et al, 2006;Klemetsen 2010;Praebel et al, 2013Praebel et al, , 2016. Profundal morphs of Arctic charr have evidently inherited traits selected for surviving in cold, dark and nutrient-poor deep-water environments, including specific adaptations in trophic morphology, behavior and growth (Klemetsen et al, 2002(Klemetsen et al, , 2006Knudsen et al, 2015). Other traits seem to a lesser degree to be under strong natural selection, such as temperature preference and vision capabilities (Siikavuopio et al, 2014;Kahilainen et al, 2016).…”
Section: This Volume)mentioning
confidence: 99%
“…Based on recent ecological and genetic studies, deep-water morphs of Arctic charr and whitefish are replicated in several locations and appear to originate locally (Østbye et al, 2006;Knudsen et al, 2006;Klemetsen 2010;Praebel et al, 2013Praebel et al, , 2016. Profundal morphs of Arctic charr have evidently inherited traits selected for surviving in cold, dark and nutrient-poor deep-water environments, including specific adaptations in trophic morphology, behavior and growth (Klemetsen et al, 2002(Klemetsen et al, , 2006Knudsen et al, 2015). Other traits seem to a lesser degree to be under strong natural selection, such as temperature preference and vision capabilities (Siikavuopio et al, 2014;Kahilainen et al, 2016).…”
Section: This Volume)mentioning
confidence: 99%
“…The anadromous individuals from the three watercourses appear to grow well, reaching sizes of >400 mm by age 6 years as seen in other northern populations (Dempson & Green, ; Johnson, ; Klemetsen et al ., ; Rikardsen et al ., ; Rubin, ). Arctic charr are able to sustain positive growth even at very low water temperatures (Knudsen et al ., ), which is clearly supported by the growth pattern of anadromous individuals from the Greenland watercourses studied here. Further, the anadromous individuals ( i.e ., high δ 34 S values) seem to mature at a larger size, which is typically seen elsewhere (Dempson & Green, ; Rikardsen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The offspring of two sympatric Arctic Char Salvelinus alpinus morphs exhibited incongruent growth patterns in Lake Fjellfrøsvatn, Norway (Knudeson et al. ). Knudeson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Knudeson et al. () suggested that the divergent growth patterns were due to differences in habitat use whereby one morph occupied the profundal zone and exhibited consistent growth rates and the other morph occurred in the littoral zone and exhibited seasonal fluctuations in growth. Early‐ and late‐run hatchery kokanee are stocked in the same locations in LPO and are thought to occupy the same habitat type (limnetic zone) based on standard midwater trawl surveys.…”
Section: Discussionmentioning
confidence: 99%